The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1525-1446.2007.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical, Psychosocial, and Socioeconomic Concerns of Urban Youth Living With Diabetes

Abstract: Offering emotional and practical support to young adults coping with diabetes is key to ensuring adequate medical management as they move into the adult system and assume full responsibility for their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…Indeed, themes related to social support were commonly voiced by both youth and their parents, similar to other qualitative findings (22). To explain this phenomenon, Allen and Gregory (5) discuss young adult independence as a myth: despite increasing self-management skills and a growing desire for autonomy, emerging adults often continue to rely on family and friends.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Indeed, themes related to social support were commonly voiced by both youth and their parents, similar to other qualitative findings (22). To explain this phenomenon, Allen and Gregory (5) discuss young adult independence as a myth: despite increasing self-management skills and a growing desire for autonomy, emerging adults often continue to rely on family and friends.…”
Section: Discussionsupporting
confidence: 85%
“…As in other samples of emerging adults with diabetes (22,25), the participants in this study emphasized the importance of a good fit with an adult care provider and expressed worries about having negative interactions. Despite these concerns, young adults in the Posttransition group largely reported positive experiences, suggesting that many adult care providers adequately address young adult issues in their practice.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…A similar study of urban youth with T1D conducted by Gee and colleagues found that challenges in establishing independence as a young adult were similar to those without a chronic condition, but coping with the management of diabetes magnified the difficulties of emerging adulthood and generally resulted in poor diabetes management [3].…”
Section: Background and Rationalementioning
confidence: 98%